The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5152/balkanmedj.2016.151610
|View full text |Cite
|
Sign up to set email alerts
|

Does Short Message Service Increase Adherence to Smoking Cessation Clinic Appointments and Quitting Smoking?

Abstract: Background: Using innovative and scientific methods increases the rate of quitting in smokers. Short message service (SMS) is a communication tool widely used and well integrated in many people's daily lives. To increase adherence to appointments in smoking cessation clinics (SCC), it is thought that increased compliance could be achieved by falling outside the traditional methods. SMS has been shown to increase the compliance of patients with SCC appointments. Aims: In this study, we aimed to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…This theory is backed up by other research—in evaluations after one of the free distribution periods (which can last up to 1.5 years), it was found that some of the patients had not even started to use the medication prescribed. In another recent national study, Önur et al 21 found the quit rate during a paid medication period to be 25% at the 6th month; and that each member of the quitter group had followed up with control visits at least once. It is worth mentioning that the mean participant ages were different between these studies: 35 years for the Benli et al study and 45 years for the Önür et al This variable may be one of the factors for the difference in quit rates; as previous research has shown that older patients are more likely to have symptoms from long-term smoking and are thus more motivated to quit 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This theory is backed up by other research—in evaluations after one of the free distribution periods (which can last up to 1.5 years), it was found that some of the patients had not even started to use the medication prescribed. In another recent national study, Önur et al 21 found the quit rate during a paid medication period to be 25% at the 6th month; and that each member of the quitter group had followed up with control visits at least once. It is worth mentioning that the mean participant ages were different between these studies: 35 years for the Benli et al study and 45 years for the Önür et al This variable may be one of the factors for the difference in quit rates; as previous research has shown that older patients are more likely to have symptoms from long-term smoking and are thus more motivated to quit 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we evaluated patients at their third month and found the quit rate to be 37.9%. In other national studies, the quit rate in the short-term was found to be 25% on average 20,22 . However, in international studies that rate was found to be higher 23,24 or similar 25 .…”
Section: Discussionmentioning
confidence: 70%
“…Yaşar et al found that smoking cessation rates increased significantly in those who received pharmacological treatment for a sufficient period of time [ 24 ]. Tural Önür et al concluded that the success of quitting is higher in patients who came to follow-up appointments [ 29 ].…”
Section: Discussionmentioning
confidence: 99%